Editorial Board and Table of Contents - Bukantis, Arūnas (Vilnius University Proceedings, 2020)
The conference is dedicated to the 250th anniversary of meteorological observations, that started in 1770. The observations were performed at the Astronomical Observatory of Vilnius University and supervised by Rector Martynas Počobutas-Odlianickis. The presentation share experiences gained from monitoring climate change and addressing current climate change issues related to threats for the national environment, economy and human well-being, also include discussions about the implementation of climate change policy objectives and other topics.